Peran Manajemen Sumber Daya Manusia Islam dalam Meningkatkan Kinerja Karyawan di Kantor Kota Medan Bagian BPKAD (Badan Pengelolaan Keuangan Dan Aset Daerah) - Mutiara Rahmah; Chuzaimah Batubara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This journal analyzes the role of human resource management (HRM) in improving employee performance at the Medan City Mayor's Office, specifically in the BPKAD department. A qualitative method was employed, utilizing interviews and observations of the employees. The findings of this research reveal that HRM based on Islamic principles has beneficial effects on employees' performance in the BPKAD department of the Medan City Mayor's Office. Islamic human resource management is implemented through several principles, such as fair and transparent decision-making, emphasis on social justice, employee capacity building through training and development, and appreciation of diversity and inclusion. In the context of the BPKAD department at the Medan City Mayor's Office, the implementation of Islamic human resource management has provided significant benefits. Employees feel more valued, appreciated, and motivated to achieve organizational targets. They also reported improvements in work quality, team collaboration, and organizational communication. This research concludes that the application of human resource management principles based on Islamic values can serve as an effective framework for enhancing employee performance. The practical implication of this study is that organizations, including the Medan City Mayor's Office, can adopt human resource management principles rooted in Islamic values to improve employee productivity and satisfaction.